Finance and economic concepts/edited by S. L. Lodha - "Lodha, S. L. (ed.)" (New Delhi, 1977)
This book of readings aims at an ex position of some of the most important economic concepts of a basic nature. The essays included, without excep tion, are written by well known econo mists. In a few cases, the contributions have been taken from material prepared by internationally known organisations or institutions. Care has been taken to see that the conributions included in the readings are written in a simple and lucid style. The book has been planned with the undergraduate and graduate students in mind. But it will also prove to be useful to more advan ced readers and practising economists.
Keywords: Monetary policy